The heterogeneity of vascular cognitive impairments and the issues of therapy - Elena Anatolyevna Katunina (Неврология, нейропсихиатрия, психосоматика)
Vascular cognitive impairments (CIs) are heterogeneous in the mechanism of their occurrence and may develop in different extent of brain damage, in different locations, and the number of foci. Their etiological factors are various. The mechanism for the development of CIs may be associated with impairments of both per se the structures responsible for cognitive functions (frontal cortex, subcortical-cortical interactions, and hippocampus) and deafferentation of the cortex and limbic structures due to periventricular white matter lesion or local lesion of the basal ganglia and thalamus. The pattern of CIs depends on the predominant involvement of cortical or subcortical regions or their combinations. The progression of CIs is also variable. In chronic cerebral circulatory insufficiency, CIs develop gradually over several years. Poststroke CIs manifest themselves acutely or subacutely. 6-27% of patients are diagnosed with dementia 3 months after acute cerebrovascular accident. The risk of subsequent dementia is 7% within the first year and 48% after 25 years.The paper reviews the most important trials of citicoline used in CIs. The drug has a multicomponent activity spectrum that permits its use in CIs of varying genesis. By taking into account its good tolerability and safety, the drug may be recommended for a wide circle of patients, including for elderly patients with comorbidity.